2012
DOI: 10.1371/journal.pone.0039923
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Social Isolation, Restraint, and Hindlimb Unloading to Changes in Hemodynamic Parameters and Motion Activity in Rats

Abstract: The most accepted animal model for simulation of the physiological and morphological consequences of microgravity on the cardiovascular system is one of head-down hindlimb unloading. Experimental conditions surrounding this model include not only head-down tilting of rats, but also social and restraint stresses that have their own influences on cardiovascular system function. Here, we studied levels of spontaneous locomotor activity, blood pressure, and heart rate during 14 days under the following experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
(32 reference statements)
8
18
0
Order By: Relevance
“…S1). This finding was surprising but consistent with a recent report that simulated weightlessness (14d) also leads to increased locomotion relative to ambulatory controls after a transient initial period of reduced motor activity 31 . Furthermore, the Validation FLT mice exhibited a rapid, repetitive running behavior, which was not observed in the Experimental mice ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…S1). This finding was surprising but consistent with a recent report that simulated weightlessness (14d) also leads to increased locomotion relative to ambulatory controls after a transient initial period of reduced motor activity 31 . Furthermore, the Validation FLT mice exhibited a rapid, repetitive running behavior, which was not observed in the Experimental mice ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, several studies have focused on deciphering rodent locomotion and exploration after a period of social deprivation. Some of them showed that isolation can cause a reduction in spontaneous locomotor activity during night-time [42], but others did not find these alterations [43]. No consistent results have been found in locomotor exploration in the open field test (OFT) either: some authors found higher exploration rates [23,43], but others revealed no differences [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the locomotor activity level increases with motivation and exploratory behaviors, such as food seeking [ 32 ] or environmental stimuli [ 33 ]. The locomotor activity in rodents increases significantly after the start of the dark phase alongside the increase in feeding behavior, before decreasing gradually toward the light period [ 34 ].…”
Section: Discussionmentioning
confidence: 99%